A novel method for high efficiently lapping of rounded diamond cutting tools. (1st January 2011) - Li, Z.Q.; Han, J.C.; Zong, W.J.; Sun, T.; Dong, S.
Rounded diamond cutting tools are widely used in ultra-precision cutting. The lapping quality of nose arc plays a very important role on the accuracy of the machined surface. However, the diamond has strong anisotropy, which is embodied in the nose arc of rounded diamond cutting tools. Therefore, simple cylindrical lapping is not an efficient method to lap the nose arc of the rounded tools. It is urgent to find a best way to lap the nose arc with high precision and efficiency. Firstly, based on periodic bond chain (PBC), a ratio model of material removal rate is built for nose arc of diamond cutting tools. And then, the optimal lapping direction is obtained. Second, two novel lapping methods are proposed according to the formula of material removal amount: one is variation of lapping pressure for uniform material volume removing and the other is variation of lapping time. Lastly, the design criterion for rounded diamond cutting tools is presented. It is recommended to use the tool with crystal plane 110 as rake face and flank face.